Howard Watkins' Retirement from Fresno-Merced Counties Legal Services Dinner at Yen Ching Restaurant - Watkins, Howard::::::::: (1985)
Howard Watkins holding appreciation gift with clock and plaque for my work at legal services 1973-1985